Semi-continuous anaerobic co-digestion of vegetable waste and cow manure: a study of process stabilization - Miramontes Martínez, Luis Ramiro; Gómez González, R.; Botello Álvarez, José Enrique; Escamilla Alvarado, Carlos; Albalate Ramírez, Alonso; Rivas García, Pasiano (Universidad Autónoma Metropolitana, 2020)
The anaerobic digestion of vegetable waste (VW) often shows the accumulation of fatty acids and low bu ering capacity that promotes instability and low methane productivity. This work evaluated the anaerobic co-digestion of VW with cow manure (CM) as a strategy to improve the process stability. As a reaction system, a 4 L semi-continuous stirred tank reactor with an HRT of 20 days and fed with a substrate formulation of 40 g of VS was used in two periods: 34 days of VW mono-digestion and 26 days of VW:CM co-digestion. The mono and co-digestion processes were numerically evaluated through three analysis tools: a proposed co-digestion model embedded in the Anaerobic Digestion Model No. 1 structure, statistical process control theory, and modeling the pH dynamics as the response of a first-order linear system to an impulse manipulation. The mono-digestion 259 Crecimiento, sobrevivencia y adaptación de Bifidobacterium infantis a condiciones ácidas (Growth, survival and adaptation of Bifidobacterium infantis to acidic conditions) L. Mayorga-Reyes, P. Bustamante-Camilo, A. Gutiérrez-Nava, E. Barranco-Florido y A. AzaolaEspinosa process showed yields of 0.381 L CH4 L digester 1d 1, which increased by 14% during co-digestion. The results indicated that in VW:CM co-digestion the pH had a slower dynamical response to the daily pulse feed, keeping the pH within the statistical 265 Statistical approach to optimization of ethanol fermentation by Saccharomyces cerevisiae in the presence of Valfor® zeolite NaA stability range. The early warning indicator IA/BA (ratio between intermediate and bicarbonate alkalinity) also stayed away from the failure threshold. It was shown that the addition of CM to a mono-digestion of VW increases the bu er capacity of the system and the production of CH4, promoting a stable and e cient process.